New taxa of the weevils closely related to Dactylotus Schoenherr, 1847 (Coleoptera: Curculionidae: Entiminae) from the Sino-Tibetan Mountains - G.E. Davidian (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2021)
Dactylotinomorphus Davidian, gen. n. (Dactylotus egenus Faust, 1887, type species) is described from China. Kamius Korotyaev, 1996, stat. n., Nipponoblosyrus Korotyaev, 1996, stat. n. and Dactylotinus Korotyaev, 1996, stat. n. are increased from a subgenus to a genus rank. A key to the genera Dactylotus Schoenherr, 1847, Kamius, Nipponoblosyrus, Dactylotinus and Dactylotinomorphus gen. n. with brief morphological characteristic is given. The new genus is closely related to Dactylotinus, from which it differs in the following features: pronotum broadest somewhat distad to the middle, as a rule without constriction near of basal margin; armament of endophallus without of unpaired median postostial grater and pair clusters of spinules; collum of spermatheca distinctly divided on broad oval postcollum and narrow antecollum; coxite-stylus approximately as wide as long. The following new combinations are established (all species are transferred from the genus Dactylotus): Dactylotinus globosus (Gebler, 1829), comb. n., Dactylotinus koreanus (Korotyaev, 1995), сomb. n., Dactylotinus tshuktsha (Lukjanovitsh, 1992), сomb. n., Dactylotinus orientalis (Korotyaev et A. Egorov, 1992), сomb. n., Dactylotinus trivialis (Faust, 1885), сomb. n., Dactylotinus dsungariensis (Pelletier, 1997), сomb. n., Dactylotinus hiekei (Pelletier, 1997), сomb. n., Dactylotinus krausei (Pelletier, 1997), сomb. n., Dactylotinus trivialismoides (Pelletier, 1997), сomb. n., Dactylotinus trivalioides (Pelletier, 1997), сomb. n., Dactylotinomorphus egenus (Faust, 1887), comb. n., Dactylotinomorphus nitidulus (Faust, 1895), сomb. n., Dactylotinomorphus roborovskyi (Faust, 1887), сomb. n., Dactylotinomorphus calvus (Marshall, 1934), сomb. n., Dactylotinomorphus gonghensis (Zhang, 1993), сomb. n., Dactylotinomorphus ligulatus (Zhang, 1993), сomb. n., Dactylotinomorphus xinghaiensis (Zhang, 1993), сomb. n., Nipponoblosyrus angusticollis (Motschulsky, 1866), comb. n., Kamius kozlovi (Korotyaev, 1979), comb. n. Eight new species are described from Gansu, Sichuan and Yunnan provinces of China: Dactylotinus arborator Davidian, sp. n., D. grandis Davidian, sp. n., D. korotyaeviDavidian, sp. n., D. pelletieri Davidian, sp. n., D. roudieri Davidian, sp. n., D. zhangi Davidian, sp. n., Dactylotinomorphus arzanovi Davidian, sp. n. and D. subnudus Davidian, sp. n. Dactylotinus grandis sp. n. has the largest body among congeners; male of D. arborator sp. n. is with deep emargination on the inner margin of fore and middle tibiae in the preapical part; D. roudieri sp. n. differs in the large size of the pair of posterior sclerites in the armament of the endophallus, which is much larger than the pair of anterior sclerites; D. korotyaevi sp. n. is closely related to D. zhangi sp. n. from which differs in slightly transverse 2nd segment of the fore tarsus and clearly differs from D. pelletieri sp. n. in the great size of tubercles on the preapical part of elytra. Dactylotinomorphus subnudus sp. n. is black and nearly bared; D. arzanovi sp. n. is with distinct brownish pubescence, composed from narrow lanceolate scales and setae.